Motivasi Zikir - Musthofa Musthofa (IAIN Ponorogo, 2013)
Abstract: Motivation zikir is an encouragement to do so by way of remembering, calls, take heed, pray, read the Quran aims given to God. Zikir have diverse motivations: zikir done through the prayers done right readings, ordinances, and movements therein, beginning with standing, bowing, sitting, prostrate, tashahud and greetings, allegedly to make normal organ and smoothness of the blood in the body that cause the human body fitness. Zikir can be done to empower and organize emotions into focus, which would cause the hormones, muscles, nerves, supposedly to make the balance function of the organs of the human body, which can work with regular and normal, resulting in hormone function and emotion into directed that leads to peace of mind (soul). Zikir is done with the correct procedures to empower the limb movements may lead prayers fitness. Zikir is done in the right way to empower and enable the muscles, nerves and hormones can lead to peace of mind or soul.